The relationship between fear of recurrence and depression in patients with cancer: The role of invasive rumination and catastrophizing - Quan, Lijuan; Wang, Xinxin; Lu, Wei; Zhao, Xintong; Sun, Jialei; Sang, Qingsong (Frontiers in Psychiatry, 2022)
Objective: To examine the relationship between fear of recurrence and depression in cancer patients. Methods: Two hundred and fifty-nine participants completed self-report questionnaires, including Fear of Progression Questionnaire - Short Form, Rumination Inventory, Cognitive emotion regulation questionnaire - Chinese version and the Center for Epidemiological Studies Depression Scale. Results: Fear of recurrence in cancer patients is at a moderate level, and the level of depression is significantly higher than that of the normal population. Fear of recurrence, invasive rumination, catastrophizing and depression in cancer patients are significantly positively correlated. The level of fear of recurrence in cancer patients is a significant positive predictor of the level of depression. Invasive rumination plays a partial mediating role between the fear of recurrence and depression in cancer patients, that is, fear of recurrence directly affects depression, and fear of recurrence indirectly affects depression through invasive rumination. Catastrophizing plays a moderating role in the mediation model in which fear of cancer recurrence affects depression through invasive rumination. Conclusions: Invasive rumination plays a mediating role between fear of recurrence and depression in cancer patients. Catastrophizing moderates the relationship between fear of recurrence and depression, as well as the relationship between invasive rumination and depression.